THE EFFECT OF CONDITIONED-MEDIUM HUMAN ADIPOSE-DERIVED MESENCHYMAL STEM CELL IN APOPTOSIS OF BLADDER CANCER CELLS - Mawdudi, Ari Alauddin; Hidayatullah, Furqan; Bachtiar, Indra; Rachman, Arif; Putri, Indri Lakhsmi; Castiglione, Fabio; Djatisoesanto, Wahjoe; Hakim, Lukman (Indonesian Journal of Urology, 2021)
Objective: To determine the effect of conditioned medium human Adipose-Derived Mesenchymal Stem Cells (CM-hADMSC) on apoptosis of urothelial bladder cancer cells. Material & Methods: Bladder (5637) cancer cell lines cultured in conditioned media harvested from human adipose-derived mesenchymal stem cells (hADMSC). Flow cytometry tests were carried out using the Flowcytometry Acquisition cell sorting (FACS) Calibur to measure apoptosis. Results: There was a significant difference in the percentage of late apoptosis in the group receiving culture medium treatment: CM-hADMSC 1: 1 to the entire study group. Further analysis revealed no difference in the average percentage of late apoptosis in groups exposed to culture medium: CM-hADMSC 1: 2 and culture medium: CM-hADMSC 1: 4 (p> 0.05). Conclusion: CM-hADMSC at a 1: 1 dose concentration to culture medium obtain a significant increase of apoptosis in bladder cancer cells.